The Effect of Accounting Conservatism and Cost of Debt on Tax Avoidance with CSR as a Moderation Variable - Hidayatulah, Azizi Aidytya; Ratnawati, Vince; Rusli; Sari, Ria Nelly (Archives of Business Research, 2025)
This study examines the impact of accounting conservatism and the cost of debt on corporate tax avoidance, with Corporate Social Responsibility (CSR) considered as a moderating factor. The research is based on secondary data obtained from annual and sustainability disclosures of firms operating in the energy sector and listed under the IDX-IC classification on the Indonesia Stock Exchange. A purposive sampling technique was employed, yielding 105 firm-year observations from 35 companies spanning the 2021–2023 period. The analytical framework employed is moderated regression analysis. The findings reveal that accounting conservatism plays a significant role in influencing tax avoidance behavior, whereas the cost of debt does not demonstrate a measurable impact. Additionally, CSR effectively strengthens the link between accounting conservatism and tax avoidance, but fails to moderate the relationship between the cost of debt and tax avoidance.